2020
DOI: 10.2341/18-176-l
|View full text |Cite
|
Sign up to set email alerts
|

Properties of New Glass-Ionomer Restorative Systems Marketed for Stress-Bearing Areas

Abstract: SUMMARY Objectives: The purpose of this study was to evaluate the properties (fracture toughness, surface hardness) of newer conventional glass-ionomer restorative materials that are marketed for posterior stress-bearing areas compared with more traditional glass-ionomer restorative materials marketed for non–load-bearing areas and composite-resin restorative materials. Methods and Materials: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…Among the coating strategies, Hotta et al found that the application of light-polymerised bonding agents helped to limit water movement across cement surface, especially within the first month of maturation [21]. This clear, self-adhesive, light-cured resin EQUIA Forte coat has single dispersion nanofillers in the matrix and a new cross linking monomer chemistry, rendering improved polymerisation, producing a tougher resin matrix [12]. This coating is speculated to toughens and protects the EQUIA Forte restorative system by infiltrating the GIC surface, thus filling cracks and porosities [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the coating strategies, Hotta et al found that the application of light-polymerised bonding agents helped to limit water movement across cement surface, especially within the first month of maturation [21]. This clear, self-adhesive, light-cured resin EQUIA Forte coat has single dispersion nanofillers in the matrix and a new cross linking monomer chemistry, rendering improved polymerisation, producing a tougher resin matrix [12]. This coating is speculated to toughens and protects the EQUIA Forte restorative system by infiltrating the GIC surface, thus filling cracks and porosities [35].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, their use was limited, due to their relatively low tensile strength, abrasion resistance, hardness and poor aesthetics [11]. A recently enhanced version of high viscosity glass ionomer cement, known as EQUIA Forte Fil (GC Corporation, Tokyo, Japan), was promoted for use as a bulk-fill restorative material in class I and II cavity design in the posterior region [12]. EQUIA Forte consists of higher molecular weight polyacrylic acid to create a high strength material, resulting in a bulk-fill glass hybrid restorative structure with improved aesthetics and physical properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity to water contamination and dehydration is restricted by the application of a resin coating [22,30]. However, in the case of Ketac Universal, no benefit has been reported [21,22]. Moreover, when the matrices were removed, remnants of the cement could be observed attached to them.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be placed in one increment and offer an alternative to resin composite when it is difficult to properly isolate teeth, as they are less sensitive to humidity [7]. Unlike, early glass ionomer cements, new reinforced formulations have been developed by modifying the powder/liquid proportion and powder particle size distribution [19,20], and it is claimed that they can be used for restricted stress-bearing Class I and II restorations [10,21]. In this regard, some of the recently launched high-viscosity glass ionomer cements (HVGICs) do not require conditioning of the dental tissues prior to their placement, or protective varnishes to improve their mechanical properties [22].…”
Section: Introductionmentioning
confidence: 99%
“…Glass ionomers were first introduced in 1978 as aluminosilicate poly acrylic cement (ASPA), which can be specifically applied in atraumatic treatment [ 6 ]. The most valuable features of glass ionomer cement include fluoride release [ 14 ], the coefficient of thermal expansion compatible with tooth tissues [ 15 ], the possibility to use them in cavities without the need for bonding agents [ 16 ], and the formation of direct chemical adhesion to the tooth structure [ 17 ]. On the other hand, the lack of sufficient strength and toughness seem to constitute the most important disadvantages of glass ionomers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%